Declining incidence of invasive Streptococcus pneumoniae infections among persons with AIDS in an era of highly active antiretroviral therapy, 1995-2000. - Heffernan, Richard T; Barrett, Nancy L; Gallagher, Kathleen M; Hadler, James L; Harrison, Lee H; Reingold, Arthur L; Khoshnood, Kaveh; Holford, Theodore R; Schuchat, Anne (The Journal of infectious diseases, 2005)
Our goal was to describe trends in invasive pneumococcal disease incidence among persons with acquired immunodeficiency syndrome (AIDS) since the introduction of highly active antiretroviral therapy (HAART).
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; African Americans; AIDS-Related Opportunistic Infections; Antiretroviral Therapy, Highly Active; European Continental Ancestry Group; Female; Hispanic Americans; Humans; Incidence; Male; Middle Aged; Pneumococcal Infections; Retrospective Studies; United States